Saudi Arabian women’s social capital: Mechanisms and obstacles to formation – Field study applied to a sample of Saudi women in Riyadh – - Alkhathlan, Entesar Saud; Alahmari, Abdullah Azib (Journal of Humanities & Social Sciences, 2021)
This study examined the mechanisms and constraints of social capital formation among Saudi Women. To achieve these objectives, the researcher used a case study method and an in- depth interview tool and note the participation to collect data. The study reached many results including that the family is an important mechanism for the formation of social capital and the weak social capital consisting of kinship relations has been replaced by relations with female friends, so the resources obtained from female friends are more beneficial than the relationships of relatives. Also, social relations with neighbors are not considered social capital for the majority of the sample. Work is one of the mechanisms of social capital formation mechanisms. As for social media, it was considered one of the mechanisms of forming social capital for some and a hindrance to the formation of social capital for others. As for the resources obtained from social capital, they were represented in getting a job, moral support, obtaining facilities in various matters of life, mental health, and financial aid. As for the obstacles to forming social capital, they were weak confidence in others, as they are often confined to family, husband, and female friends, the weakness of the culture of volunteerism and its non- proliferation, and the wrong and excessive use of social media.